(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2022)
This paper presents an exploratory work with descriptive analysis of more than nine hundred women accompaniments by Socorristas of La Pampa between 2015 and 2020. First of all, the article introduce the unique Socorristas device that allows to go through its feminist methodology of situated approach. Then, advance in the analysis on a selection of social, cultural, motivational, relationship, biographical data on the women accompanied in their decision process. The intention is to investigate, and interpret from a feminist perspective, sensitive variables that are part of their daily life, showing that decisions, especially related to motherhood and abortion, are complex, multidimensional and collective constructions.